2021
DOI: 10.1007/s11627-020-10139-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of galanthamine production through elicitation and NMR-based metabolite profiling in Narcissus pseudonarcissus cv. Carlton in vitro callus cultures

Abstract: Plants are the unique sources of secondary metabolites (terpenes, phenolic and alkaloid) used as pharmaceuticals, food additives and industrial produces. However, very limited information is known about their biosynthesis in plants. Elicitors are chemicals often used to activate the accumulation of such metabolites in plant in vitro cultures. Since the ancient past, Narcissus is well-known for its ornamental purposes and medicinal versatility with diverse pharmaceutically important alkaloids including galantha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
(77 reference statements)
1
4
1
Order By: Relevance
“…Similar to our study, research on galantamine and metabolites using Narcissus pseudo narcissus , which is closely related to Narcissus gazzetta , also showed that the galantamine content is lowest in the callus. 37 However, unlike our data, this study was not able to detect a significant amount of galantamine in the root, which may be due to the different conditions for root induction. For example, unlike our tissue culture conditions, for root induction, we used cytokinin, which can act as a NAA antagonist.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Similar to our study, research on galantamine and metabolites using Narcissus pseudo narcissus , which is closely related to Narcissus gazzetta , also showed that the galantamine content is lowest in the callus. 37 However, unlike our data, this study was not able to detect a significant amount of galantamine in the root, which may be due to the different conditions for root induction. For example, unlike our tissue culture conditions, for root induction, we used cytokinin, which can act as a NAA antagonist.…”
Section: Discussioncontrasting
confidence: 99%
“…This suggests an efficient and high-yielding method for the commercial-scale production of galantamine. Similar to our study, research on galantamine and metabolites using Narcissus pseudo narcissus, which is closely related to Narcissus gazzetta, also showed that the galantamine content is lowest in the callus . However, unlike our data, this study was not able to detect a significant amount of galantamine in the root, which may be due to the different conditions for root induction.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The plantlets were cultured on MS basal medium with plant growth regulators. Plant callus as an alternative source of raw material can be induced to increase its metabolites content through several interventions, for example, by adding biotic or abiotic elicitors (Ferdausi et al, 2021), manipulating biosynthetic pathways (Inyai et al, 2021), or genetic engineering (Shi et al, 2021).…”
Section: Multivariate Analysismentioning
confidence: 99%
“…Phytochemical profiling with gas chromatography–mass spectrometry (GC–MS) has recently emerged as one of the most valuable techniques to detect and identify bioactive compounds, like alkaloids, flavonoids, tannins, phenols, steroids, terpenoids and essential oils [ 8 , 9 ]. This technique requires a low extract level to analyze metabolites with precision and reproducibility [ 10 ]. There are reports of GC–MS-based profiling of in vitro regenerated plants, like Tecoma stans [ 11 ] and Curcuma zedoaria [ 12 ].…”
Section: Introductionmentioning
confidence: 99%